2022
DOI: 10.1177/14713012211073205
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and its impacts on the intimate, sexual couple relationship: A systematic review of qualitative research studies

Abstract: Objective There is growing evidence for the need to recognize persons with dementia as sexual beings who wish to continue expressing their sexuality, including within their couple relationship. The aim of this literature review was to investigate empirical qualitative studies that examined sexuality and sexual intimacy in the couple relationship when one spouse has dementia. Method A systematic literature review was performed in January 2021, five data bases were searched: Pubmed, MedLine, Lilacs, Scopus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…Thus, we hypothesize that those in good marriages have more to lose when their spouse develops cognitive limitations 14,15 . Our epidemiologic results complement prior qualitative studies 11,12 that identified close partners' sense of grief and anger at the loss of intimacy, both physically and intellectually or emotionally, in the face of dementia. We did not find a similar trend between marital quality and depression as related to spousal dementia.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Thus, we hypothesize that those in good marriages have more to lose when their spouse develops cognitive limitations 14,15 . Our epidemiologic results complement prior qualitative studies 11,12 that identified close partners' sense of grief and anger at the loss of intimacy, both physically and intellectually or emotionally, in the face of dementia. We did not find a similar trend between marital quality and depression as related to spousal dementia.…”
Section: Discussionsupporting
confidence: 73%
“…Prior research details the large impact of dementia on the psychosocial health of spouses and caregivers, including themes of loneliness or loss, and sadness 11,12 . Moreover, extensive qualitative and sociology research demonstrates how the quality of the marital relationship, not just presence of the relationship, can influence psychosocial well‐being among spouses of PLwD 13–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dementia diagnosis does not erase sexuality but may alter the way in which love and affection are given and received. Embracing persons with dementia as sexual beings, who have something to say about their own sexuality, and who have physical and intimate needs is essential for understanding their lived experience, in all its dimensions (Albert et al, 2022; D’Cruz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition that dementia is not experienced in isolation by the individual but within a relationship recognizes that couple intimacy is complex and paradoxical, and the expression of sexual intimacy often emerges as ambivalent and ambiguous (Albert et al, 2022; Youell et al, 2016). A significant proportion of people with dementia live in their own homes, and are often cared for by their spouses, which means the couple relationship is often sustained throughout the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%